(untitled) (Bangladesh Journal of Microbiology, 2023)
Gram-negative Pseudomonas spp. particularly P. aeruginosa is an important pathogen in hospitalized patients, contributing to the morbidity and mortality due to its multiple resistance mechanisms. The present study was undertaken to determine the characteristics of Pseudomonas spp. isolated from pus of patients admitted in a local diagnostic center, Dhaka, Bangladesh. A total of 14 clinical isolates were obtained. Detailed biochemical tests, antibiotic resistance pattern and class 1 integron gene profiling were successfully performed. All isolates (100%) showed resistance against amoxicillin-clavulanate, ampicillin, ciprofloxacin, cephalexin, ceftriaxone, kanamycin, nitrofurantoin and rifampicin. About 35% of the isolates (n=5) showed resistance against Amoxicillin-clavulanate, ampicillin, azithromycin, amikacin, ciprofloxacin, cephalexin, co-trimoxazole, ceftriaxone, imipenem, kanamycin, nitrofurantoin and rifampicin. Only 28.5% isolates (n=4) were sensitive to Imipenem. Plasmid was observed in none of the isolates, whereas 50% of the isolates carried Class 1 Integron gene. The presence of mobile genetic element is an added threat as this enables transfer of resistance genes to sensitive isolates. The findings of this study are significant from a public health viewpoint as therapeutic options become restricted. Bangladesh J Microbiol, Volume 39, Number 1, June 2022, pp 15-19